2009
DOI: 10.1002/jemt.20670
|View full text |Cite
|
Sign up to set email alerts
|

In situ transmission electron microscopy and ion irradiation of ferritic materials

Abstract: The intermediate voltage electron microscope-tandem user facility in the Electron Microscopy Center at Argonne National Laboratory is described. The primary purpose of this facility is electron microscopy with in situ ion irradiation at controlled sample temperatures. To illustrate its capabilities and advantages a few results of two outside user projects are presented. The motion of dislocation loops formed during ion irradiation is illustrated in video data that reveals a striking reduction of motion in Fe-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…[63][64][65][66][67][68][69] Such experiments allow irradiation concurrent with observation in a transmission electron microscope. A black dot damage microstructure is seen to dominate irradiated ferritic/martensitic alloys up to temperatures of at least 300°C.…”
Section: Mev Kr Irradiation Of Fe-cr Ferritic/ Martensitic Alloymentioning
confidence: 99%
“…[63][64][65][66][67][68][69] Such experiments allow irradiation concurrent with observation in a transmission electron microscope. A black dot damage microstructure is seen to dominate irradiated ferritic/martensitic alloys up to temperatures of at least 300°C.…”
Section: Mev Kr Irradiation Of Fe-cr Ferritic/ Martensitic Alloymentioning
confidence: 99%
“…Ion irradiation is known to differ from neutron/reactor irradiation in multiple aspects, including dose rate and probabilistic and spatial distributions of primary defects (those generated directly during collision cascades, prior to long range diffusion and interactions). In the case of in-situ TEM (Transmission Electron Microscopy) ion irradiation, an advanced experimental technique that allows real-time observation of microstructural/defect evolution during simultaneous ion irradiation, [9][10] the small (tens to a few hundred nanometer) thickness of a TEM foil and the related surface sink effect on mobile defects represent another key aspect distinct from neutron irradiation. Given these major differences, a significant question arises: can the microstructural/defect evolution be matched across different irradiation conditions?…”
Section: Introductionmentioning
confidence: 99%
“…In designing this study, we have had the opportunity to utilize a specialized transmission electron microscope (TEM) facility with in situ ion irradiation capabilities. This facility, the IVEM‐Tandem Facility at Argonne National Laboratory, was designed specifically to study ion‐induced amorphization and other structural changes in materials as observed using TEM techniques in real time and precisely correlated with ion dose (Kirk et al. 2009).…”
Section: Introductionmentioning
confidence: 99%